24th Psychology Days in Zadar: Book of Selected Proceedings - ompadmin; Macuka, Ivana (2026)
The Psychology Days in Zadar is a distinguished international conference organised biennially by the Department of Psychology at the University of Zadar. Since its beginnings, the conference has grown from a regional academic gathering into a highly regarded international event, attracting researchers and practitioners from across Europe and beyond. Its continued succ ess reflects both a strong commitment to scientific excellence and the enthusiasm of its participants, whose engagement shapes and sustains its reputation.The 24th Psychology Days in Zadar, held from 26 to 28 May, once again brought together a dynamic and diverse academic community eager to exchange knowledge, present cutting-edge research, and engage in meaningful discussions on contemporary psychological issues. Organised by an international scientific and organisational committee, this year’s conference upheld its tradition of fostering intellectual collaboration and innovation.The Book of Selected Proceedings presents a carefully curated selection of empirical studies showcased at the conference, alongside invited lectures offering theoretical and review perspectives. Researchers from various countries contributed to this volume, presenting 12 papers across keynote lectures, symposia, and oral presentations. Each paper underwent a rigorous double-blind review process, ensuring the publication maintains the highest academic standards. The selected research spans a wide range of psychological disciplines, including personality psychology, educational psychology, developmental psychology, and clinical psychology - offering valuable insights for researchers and practitioners alike.
Keywords: parental burnout; emotional crying; determinants of successful ageing; humour; Rasch analysis; grit; Dual Coding Theory; basic psychological needs; actively open-minded thinking (AOT); Wason selection task; music; pregnancy